Evaluation of feed resources availability and use for sustainable livestock production in the Northern highland systems of Lao PDR - Philp, Joshua Neil Monty; Soytavanh, Mienmany; Atieno, Mary; Jalonen, Riina; Mekonnen, Kindu; Gebreyes, Million; Pazos, Mateo; Peters, Michael (2024)
The Government of Laos has intensified support for livestock producers to improve their livelihoods by intensifying cattle production to meet the local and regional market demand, however the provision of adequate and nutritious feed for sustainable cattle production remains challenging in highland mixed farming systems of Northern Laos. Addressing this requires context-specific feed interventions. In the frame of the CGIAR initiative on Mixed Farming Systems, an assessment aiming to characterize livestock feed resources in highland mixed farming systems was conducted using the Gendered Feed Assessment Tool (G-FEAST). G-FEAST assessment was conducted in 4 villages in Northern Laos, 2 villages in Phonxay district, Luang Prabang province and 2 villages in Nonghet district, Xieng Khouang province, from 13th to 25th August 2023. The application of the G-FEAST tool enabled the characterization of livestock feeding systems in highland mixed farming systems whilst examining the potential for gendered differences in management and constraint ranking. Participating households mainly practiced extensive pastoral agriculture in which cattle account for most tropical livestock units kept and derive most of their nutrition from grazing pastures, including significant areas of planted forage. However, the varieties of forage cultivated are not productive during the extended dry season and feed shortages become pronounced from January until June, constraining livestock production. The assessment found that whilst women and men tended to share labor for agricultural activities, gendered differences were present in ownership and decision-making. There are opportunities for sustainable intensification of upland farming systems in Northern Laos to overcome the constraints to livestock feeding that were identified in this study. Particularly, the introduction of drought-resilient forage varieties sustained by improved seed systems, better integration of forage and tree systems, and better integration of maize and livestock systems have the potential to improve productivity and incomes of smallholder farmers.